Identificación del estreptococo beta hemolítico del grupo B (agalactiae) en las semanas 28 a 37 de gestación para prevenir sepsis neonatal en el periodo abril/mayo del 2014 - Gonzaga Erazo, Glenda Susana (2015)
Beta hemolytic streptococcus group B (agalactiae) (GBS) is a bacterium that is part of the normal flora of the female genital tract. In the pregnant woman, the bacteria may be present due to the physiological changes of pregnancy and it also causes serious infections in the mother and the baby. For the reason explained, this research: to identify beta hemolytic group B streptococcus agalactiae in pregnants of 28 to 37 weeks, to determine antimicrobial sensitivity using the anti-biogram test in cases that were positive and to report them to the health personnel. This research was descriptive-transverse; women who were in the third trimester of pregnancy were chosen in a sample of 50 patients (n= 50). They were evaluated with the method of cultivation, the identification scheme, the CAMP test and anti-biogram in the vaginal fluid sample getting the following results: a 96% (n = 48) of the cases were negative and the 4% (n=2) were positive, for these latter ones the antimicrobial sensitivity was performed showing a 100% of sensitivity to penicillin and Cefazolin. To conclude the analysis of the present study, this test should be performed routinely before the birth to prevent most infections in the newborn with prophylaxis medication during the childbirth Key words: Beta hemolytic streptococcus group B, pregnancy, vaginal discharge, sepsis.